Studies on mononuclear chelates derived from substituted Schiff-base ligands (part 6): synthesis and characterization of a new 3-ethoxysalicyliden-p-aminoacetophenoneoxime and its complexes with cobalt(II), niekel(II), copper(II) and zinc(II) - Canpolat, Erdal; Kaya, Mehmet; Oztuerk, Omer Faruk (Taylor & Francis Ltd, 2007)
Schiff-base complexes of cobalt(II), nickel(II), copper(II)and, zinc(II) with 3-ethoxysalicyliden-p-aminoacetophenoneoxime (HL) were prepared and characterized on the basis of elemental analyses, 1R, H-1- and C-13-NMR, electronic spectra, magnetic susceptibility measurements, molar conductivity and thermogravimetric analyses (TGA). A tetrahedral geometry has been assigned to the complexes.
Keywords: Schiff bases; cobalt(II); nickel(II); copper(II); zinc(II) complexes